Endothelial progenitor cells derived from embryonic stem cells prevent alveolar simplification in a murine model of bronchopulmonary dysplasia - Kolesnichenko, Olena A.; Flood, Hannah M.; Zhang, Yufang; Ustiyan, Vladimir; Cuervo Jimenez, Hayde K.; Kalin, Tanya V.; Kalinichenko, Vladimir V. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Vascular remodeling and compromised alveolar development are hallmarks of chronic pulmonary diseases such as bronchopulmonary dysplasia (BPD). Despite advances in neonatal healthcare the number of BPD cases worldwide continues to increase. One approach to overcoming the premature arrest in lung development seen in BPD is to stimulate neonatal angiogenesis via delivery and engraftment of endothelial progenitor cells (EPCs). One such population is resident to the pulmonary microvasculature and expresses both FOXF1 and c-KIT. Previous studies have shown that c-KIT+FOXF1+ EPCs are highly sensitive to elevated levels of oxygen (hyperoxia) and are decreased in premature infants with BPD and hyperoxia-induced BPD mouse models. We hypothesize that restoring EPCs through transplantation of c-KIT+FOXF1+ EPCs derived in vitro from pluripotent embryonic stem cells (ESCs), will stimulate neonatal angiogenesis and alveolarization in mice with hyperoxia-induced lung injury. Methods: Utilizing a novel ESC line with a FOXF1:GFP reporter, we generated ESC-derived c-KIT+FOXF1+ EPCs in vitro. Using a second ESC line which contains FOXF1:GFP and tdTomato transgenes, we differentiated ESCs towards c-KIT+FOXF1+ EPCs and tracked them in vivo after injection into the neonatal circulation of hyperoxia-injured mice. After a recovery period in room air conditions, we analyzed c-KIT+FOXF1+ EPC engraftment and quantified the number of resident and circulating endothelial cells, the size of alveolar spaces, and the capillary density after EPC transplantations. Results and conclusion: Herein, we demonstrate that addition of BMP9 to the directed endothelial differentiation protocol results in very efficient generation of c-KIT+FOXF1+ EPCs from pluripotent ESCs. ESC-derived c-KIT+FOXF1+ EPCs effectively engraft into the pulmonary microvasculature of hyperoxia-injured mice, promote vascular remodeling in alveoli, increase the number of resident and circulating endothelial cells, and improve alveolarization. Altogether, these results provide a proof-of-principle that cell therapy with ESC-derived c-KIT+FOXF1+ EPCs can prevent alveolar simplification in a hyperoxia-induced BPD mouse model.